Letrasilta, a new genus for the Striatella cernyi Volynkin species-group with description of a new species from Xizang, China, and a replacement name for the genus group name Striatella Volynkin & S.-Y. Huang, 2019 (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Huang, Si-Yao; Volynkin, Anton V.; Yin, Xiong-Yan; Zhang, Yu-Long; Fan, Xiao-Ling; Pan, Zhao-Hui; Wang, Min (Zootaxa, 2023)
The name Striatochrista nom. n. is introduced as replacement for Striatella Volynkin & S.-Y. Huang, 2019. A new genus, Letrasilta S.-Y. Huang & Volynkin gen. n. is erected to include the Striatella cernyi species-group with the new species, L. ratnasambhava S.-Y. Huang, Volynkin & Yin sp. n. from Xizang, southwestern China designated as the type species. Based on the molecular phylogenetic analysis, the new genus is found to be sister to the clade (Aberrasine + ((Indiania + Idopterum) + Striatochrista nom. n.)) but is distinguished from all the relevant genera by the unique genitalia features. Letrasilta cernyi (Volynkin, 2018) comb. n. is also reported from India for the first time. Adults and genitalia of the aforementioned taxa are illustrated. A checklist of the genus Striatochrista is also provided.